Looking at The Legal Philosophy Regarding The Grabbing of Pantai Raja Customary Land - R Mustar Lofi (Universitas Semarang, 2025)
This study analyzes land conflicts in Riau Province, focusing on disputes among corporations, between corporations and local communities, and with indigenous customary law communities. These conflicts are triggered by environmental degradation, land encroachment, overlapping land claims, and administrative boundary disputes. The urgency of this study lies in its legal and social implications, including prolonged litigation, weakening of state authority, social unrest, and disruption of community livelihoods. Specifically, the research seeks to answer how land conflict resolution mechanisms in Riau can be made more effective, inclusive, and sustainable, with a particular emphasis on the conflict in Pantai Raja as a representative case. Employing a qualitative research method, the study examines legal frameworks, government policies, and empirical data from case studies to explore how customary land rights intersect with state-issued land use permits. The findings show that responses to conflict are often reactive, initiated only after public outcry or demonstrations. This reactivity stems from unclear governance structures, weak early mediation mechanisms, and minimal community involvement, which in turn exacerbate tensions and obstruct sustainable resolution efforts. The study contributes to the development of legal theory in agrarian law and conflict resolution by proposing an integrated and anticipatory conflict resolution framework. A structured collaboration model is introduced, wherein plantation companies cooperate with village-owned enterprises (BUMDes) under legal and institutional arrangements that ensure fair benefit-sharing, recognition of indigenous land rights, and participatory decision-making. This model aims not only to resolve existing conflicts but also to inform future policy-making and strengthen the legal framework for managing land disputes in Indonesia.